Acute abdomen and perforated duodenal ulcer in an adolescent: case report (2018)
Acute abdominal pain is one of the most frequent reasons for consultation in emergency departments. Its causes are diverse and are divided into surgical and medical. Surgical causes may be traumatic, obstructive or inflammatory. The last category includes perforated hollow viscus as a complication of duodenal ulcer, a rare condition in pediatrics.This paper presents the case of a previously healthy 14-year-old adolescent who attended the emergency department due to the sudden onset and rapid progression of abdominal pain in the right hypochondrium, which radiated to the lower back on the same side. This condition was associated with vasovagal symptoms and was initially managed as urolithiasis, considering clinical deterioration and obvious signs of generalized peritonitis, which required a diagnostic laparoscopy followed by laparotomy by pediatric surgery.Perforated duodenal ulcer was diagnosed during the procedure as the cause of the symptoms. This paper intends to show the experience of clinical cases with an initial diagnostic error and include complicated duodenal ulcer as a differential diagnosis.